Potato Flour Substitution: Sensory, Physical, and Chemical of Fried Dumpling Skin - Christina Hening Setyo Wulandari; Octavianti Paramita (TEKNOBUGA: Jurnal Teknologi Busana dan Boga, 2026)
This study aims to analyze the sensory characteristic and chemical content of fried dumpling skin as an effort to develop local based product. Four levels of potato flour substitution (0%, 10%, 20%, and 30%) were included in the Completely Randomized Design (CRD) to be analyzed through ANOVA at 5% level of significance then continued by Duncan’s Multiple Range Test. 3 expert panelists participated in organoleptic test and 80 untrained panelists participated in hedonic test. The result indicated that expert panelists found there was no significant on each treatment, whereas the untrained panelists found different significancy to each treatment. The best treatment according to hedonic test was 10% substitution. In terms of nutrition, the product that substituted 30% potato flour had the highest water and kalium value. Color analysis using CIE L*a*b* revealed that potato flour substitution can decrease L* (lightness), and increase a* (redness), and b* (yellowness).